Portfolio strategies of life science venture capital firms in the USA and Europe - Holger Patzelt; Dodo zu Knyphausen-Aufseß; Yasmin Habib (Max Planck Institute of Economics, 2005)
Motivated by the different development stages of both, the venture capital (VC) as well as the life science industry in the USA and Europe, we investigate portfolio strategies of US-American and European VC firms active in this sector. We analyse portfolios of 88 VCs financing a total of 1050 life science ventures. Our results show that US life science VCs are equally likely to have a focus on early stage ventures and to diversify across investment stages as their European counterparts. However, the latter invest more in the US industry than vice versa, more in traditional life science technologies developing therapeutics and diagnostics, and less in new medical technology and healthcare/IT firms. Regarding the VCs' internationalisation strategies, our results reveal that VCs investing globally and US VCs focusing on their home market invest more in medical technology and healthcare/IT and less in diagnostics firms than European VCs with European investees only. We conclude that European life science ventures developing medical and healthcare/IT technologies should internationalise early enough into the USA in order to access the US VC market. Therapeutics and diagnostics companies in the USA, on the other hand, may find good opportunities to raise VC in Europe.
Keywords: 330; Venture Capital; Europe; USA; portfolio; biotechnology; life science; healthcare; medical technology